LOW DOSE REGIMEN AND FORMULATION OF A 5-METHYL-1,2,4-OXADIAZOL-3- YL COMPOUND - MERGOTT Dustin James; KIELBASA William Brian (2023)
ABSTRACT The present invention provides a compound of Formula I:, or a pharmaceutically acceptable salt thereof, wherein the compound of Formula I, or pharmaceutically acceptable salt thereof is administered orally with a total dose of the compound of 0.1 mg/day to 5 mg/day, useful for treating a neurodegenerative disease, including neurodengenerative tauopathies, such as Alzheimers disease, frontotemporal dementia, corticobasilar syndrome, and progressive supranuclear palsy. La presente invención proporciona un compuesto de Fórmula I: (ver Fórmula), o una sal farmacéuticamente aceptable de este, en donde el compuesto de Fórmula I, o una sal farmacéuticamente aceptable de este, se administra por vía oral con una dosis total del compuesto de 0.1 mg/día a 5 mg/día, y es útil para tratar una enfermedad neurodegenerativa, incluidas las tauopatías neurodegenerativas, como la enfermedad de Alzheimer, la demencia frontotemporal, el síndrome corticobasilar y la parálisis supranuclear progresiva.